2010
DOI: 10.1177/0013916509357696
|View full text |Cite
|
Sign up to set email alerts
|

“An Inconvenient Truth” Increases Knowledge, Concern, and Willingness to Reduce Greenhouse Gases

Abstract: Since May 24, 2006 millions of people have seen the movie "An Inconvenient Truth:'Several countries have evenproposed using the film asaneducational tool in school classrooms. However, it is not yet clear that the movie accomplishes its apparent goals of increasing knowledge and concern,and motivating people to reduce their greenhouse gas emissions.Two studies are reported, one with a sample of community moviegoers, and one witha sample ofstudents.Acrossthe two studies,results show that watching "An Inconvenie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 13 publications
4
81
0
3
Order By: Relevance
“…Indeed, those that utilise primarily cognitive/affective processes of change should be expected to encourage early stage progression, rather than behavioural change. Nolan (2010) found that An Inconvenient Truth inspired little concrete action among students who were recruited to watch it and who did not display high levels of concern about climate change beforehand, but the film did increase concern and motivation to act immediately afterwards. This might be evidence of progression from precontemplation to contemplation, or from contemplation to preparation, among an audience who were at early stages of change.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Indeed, those that utilise primarily cognitive/affective processes of change should be expected to encourage early stage progression, rather than behavioural change. Nolan (2010) found that An Inconvenient Truth inspired little concrete action among students who were recruited to watch it and who did not display high levels of concern about climate change beforehand, but the film did increase concern and motivation to act immediately afterwards. This might be evidence of progression from precontemplation to contemplation, or from contemplation to preparation, among an audience who were at early stages of change.…”
Section: Discussionmentioning
confidence: 98%
“…Akter and Bennett (2011) discovered that Australians who had seen An Inconvenient Truth were significantly more likely to report having reduced their use of motorized vehicles and/or electricity than non-viewers, and claim that the film influenced behaviour, but the study appears to show correlation rather than causality and it seems equally likely that people already engaged in climate change mitigation action are more likely to see the movie than those who are not. Individuals who saw it at a free showing organised by an NGO in the USA exhibited high levels of belief in climate change and motivation to act beforehand (Nolan, 2010). The film has, however, been incorporated into the school curriculum in several countries (Climate Crisis, undated), which makes it likely it will be seen by children at a range of stages of change with respect to lower-carbon behaviours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an empirical study, exposure to a specific information source, namely Al Gore's movie "An Inconvenient Truth," resulted in raising levels of knowledge about climate change and level of concern about climate change (Nolan 2010). This latter study used objective measures of knowledge about climate change and found a positive relationship between level of knowledge and level of concern in two small-N empirical studies.…”
Section: Informationmentioning
confidence: 95%